2019
DOI: 10.3389/fneur.2019.00187
|View full text |Cite
|
Sign up to set email alerts
|

Brain ApoA-I, ApoJ and ApoE Immunodetection in Cerebral Amyloid Angiopathy

Abstract: Cerebral amyloid angiopathy (CAA) is a common cause of lobar intracerebral hemorrhage (ICH) in elderly individuals and it is the result of the cerebrovascular deposition of beta-amyloid (Aβ) protein. CAA is frequently found in patients with Alzheimer's disease (AD), although it has an independent contribution to the cognitive deterioration associated with age. Specific apolipoproteins (Apo) have been associated with Aβ fibrillization and clearance from the brain. In this regard, in the present study, we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Consistent with the above considerations concerning endothelial dysfunction in Alzheimer's disease, ApoA -I has very recently been reported by Camacho et al [75] to play a special role in cerebral amyloid angiopathy (CAA). CAA is observed in more than 90% of patients with Alzheimer's disease, although it additionally has an independent contribution to the cognitive deterioration associated with age.…”
Section: Endothelial Dysfunction As a Therapeutic Target For Cognitivsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with the above considerations concerning endothelial dysfunction in Alzheimer's disease, ApoA -I has very recently been reported by Camacho et al [75] to play a special role in cerebral amyloid angiopathy (CAA). CAA is observed in more than 90% of patients with Alzheimer's disease, although it additionally has an independent contribution to the cognitive deterioration associated with age.…”
Section: Endothelial Dysfunction As a Therapeutic Target For Cognitivsupporting
confidence: 67%
“…CAA can be neuropathologically classified as CAA type I or type II, where type I is characterized by amyloid-β deposition in cerebral capillaries (versus type II where cerebral capillaries are not involved). The human data (from autopsy brains of 20 post-mortem cases), reported by Camacho et al, revealed that the ApoA-I immunohistochemical staining was localized strongly toward capillary walls with CAA (i.e., especially toward CAA type I pathology) [75]. Also, as alluded to above (see Abstract), the previously documented similarities in lipid composition among HDL (as well as native low-density lipoproteins (LDL) and modified LDL) and LCM/ND nanoemulsion particles can partially simulate or mimic the known heterogeneity (i.e., subpopulations or subspecies) of HDL particles (see [73] for a review).…”
Section: Endothelial Dysfunction As a Therapeutic Target For Cognitivmentioning
confidence: 94%
“…Co-deposited proteins and apolipoproteins-Aβ that is deposited in neuritic plaques and vessels is accompanied by Aβ-associated proteins, including complement proteins, serum amyloid P component, α1-antichymotrypsin, glycosaminoglycans, matrix metalloproteinase 9 (MMP9) and various apolipoproteins, such as apolipoprotein E, apolipoprotein J (also known as clusterin) and apolipoprotein A-I [133][134][135][136][137][138][139][140][141][142][143][144][145] (Table 1). When, how and at what concentrations these associated proteins are co-deposited with Aβ remain to be determined, but some of these components can accelerate or inhibit the formation of Aβ fibrils [146][147][148][149][150] .…”
Section: Aβ Peptide Length-althoughmentioning
confidence: 99%
“…We were particularly interested in studying the distribution of ApoJ in circulating lipoproteins because of its potential to participate in Aβ accumulation and clearance and modulate the balance between Aβ levels in brain vessels and parenchymal plaques [ 66 ]. In addition, ApoJ is co-deposited with fibrillary Aβ in both parenchymal plaques and vascular Aβ deposits [ 67 , 68 , 69 , 70 ]. Therefore, we first analyzed the levels of circulating total ApoJ levels, although no statistically significant differences among groups were obtained.…”
Section: Discussionmentioning
confidence: 99%